PENGARUH ACCEPTANCE AND COMMITMENT THERAPY TERHADAP PERUBAHAN KECEMASAN DAN SELFEFFICACY PADA PASIEN DENGAN HEMODIALISA DI RS SINT CAROLUS JAKARTA - Ismoyowati, Tri Wahyuni (Jurnal Kesehatan, 2018)
Background: According to the US Renal Data System at the end of 2013 a total of 441,051 patients were treated with CKD. According to Riskesdas (2013), is ranked the 10th disease that not contagious. Thenumber of CKD patients hemodialysis at Sint Carolus Hospital Jakarta increased in 2016. Patients who has lived with the hemodialysis therapy experience anxiety and decreased self-effcacy. Acceptance andCommitment therapy (ACT) therapy was one of the most ?exible and effcient therapies for dealing with anxiety and self-effcacy. Objective: This study aims to determined an the effect of ACT on changes in anxietyand Self-Effcacy in patients live with hemodialysis in Sint Carolus Hospital. Methods: The research design conducted with quasi experimental design pre-post measured. An amount of the sample were 99 respondentswith purposive sampling technique. Results: The different within test results showed signifcant changes in Anxiety and Self-Effcacy before and after intervention p = 0.000. The result of different between test havesignifcant Anxiety and Self-Effcacy changes between the ACT intervention group and the control group p = 0.000. Intervention ACT simultaneously gives effect to 25% anxiety change and Self Effcacy change25.5%. The result of Odds Ratio analysis shows that ACT intervention has an effect on decreasing Anxiety by 3 times while has been increased self effcacy by 4 times in patients having live with the hemodialysis.Conclusion: This means ACT affected the changes in anxiety and Self-Effcacy of patients that were have lived hemodialysis. Suggestion: This study has been recommended the need for further research as anindependent nurse nursing intervention in nursing care.Keywords: Acceptance and Commitment therapy (ACT) – Anxiety - Self Effcacy - Hemodialysis.